Engineering the Future of Education: Integrating Curriculum and Technology in Indonesia's Digital Age - Gagarin, Yuri; Zaskiyah Veronica; Sinta Adili; Intan Nur Fadillah; Akbar Dieva; Mardiah Astuti (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
The rapid digital transformation has placed education as a crucial sector requiring curriculum-technology integration to prepare Indonesian human resources for global competition. This study aims to examine curriculum and technology integration as a strategy for engineering Indonesian education in the digital era. Using a convergent mixed methods design parallel to library research, the study targeted educators, students, parents, and policymakers in urban, rural, and 3T areas (N=395; n=350 surveys, n=45 interviews, 6 focus groups). Instruments included validated questionnaires, semi-structured interviews, and focus group guides, analyzed using SPSS descriptive statistics and NVivo thematic coding with data triangulation. Results showed an 82% increase in student engagement and 76% increase in digital literacy through blended learning, despite infrastructure gaps (42% fast internet) and teacher training deficits (62%). Conclusions emphasize content localization, TPACK training, and stakeholder collaboration for inclusive digital transformation aligned with the Independent Curriculum.